Optimized design of a permanent magnet brushless DC motor for solar water-pumping applications - Sen, Aryadip (2025)
This paper presents a volume-optimized architecture for a brushless DC (BLDC) motor in the permanent magnet (PM) category. The proposed design minimizes the volume of the PM, achieving a 20 % reduction in material usage and lowering the overall cost of the motor without compromising performance. Efficiency improvements of up to 4.7 % over conventional BLDC motors with equivalent ratings are realized through parametric design optimization. Additionally, a sensorless control system is developed to drive the motor, reducing electronic controller complexity and cost by eliminating the need for position sensors. The control strategy, based on two voltage sensing points, accurately manages electronic commutation and speed control across a wide range, independent of motor parameters, using adaptive error optimization. The motor and solar maximum power are controlled through a single-stage three-phase inverter, making the electronic controller compact and enhancing its suitability for integrated applications. Magnetic and performance characteristics of the optimized motor are analyzed through finite element analysis (FEA). The motor prototype is manufactured in an industrial setting, and experimental validation using the developed sensorless controller demonstrates superior performance and an enhanced efficiency-to-cost ratio, making the proposed design an attractive solution for solar-powered irrigation systems.